2016
DOI: 10.1038/srep37929
|View full text |Cite
|
Sign up to set email alerts
|

Variations in abundance, diversity and community composition of airborne fungi in swine houses across seasons

Abstract: We examined the abundance, diversity and community composition of airborne fungi in swine houses during winter and summer seasons by using quantitative PCR and Illumina HiSeq sequencing of ITS1 region. The abundance of airborne fungi varied significantly only between seasons, while fungal diversity varied significantly both within and between seasons, with both abundance and diversity peaked in winter. The fungal OTU composition was largely structured by the swine house unit and season as well as by their inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 58 publications
4
68
3
Order By: Relevance
“…Importantly, air samples and nasal samples from pigs showed the same trend as the nasal swabs from pig farmers, with increased alpha diversity values in winter. Previous studies also found higher diversity in winter than in summer for both bacteria and fungi in the air in pig confinement buildings (16,17).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Importantly, air samples and nasal samples from pigs showed the same trend as the nasal swabs from pig farmers, with increased alpha diversity values in winter. Previous studies also found higher diversity in winter than in summer for both bacteria and fungi in the air in pig confinement buildings (16,17).…”
Section: Discussionmentioning
confidence: 64%
“…In winter, openings such as doors and windows are closed, and a lower ventilation rate is taken up to minimalize heat loss. There are studies that have investigated seasonal variabilities of bacteria, archaea, and fungi in the air of pig buildings, and they have found a seasonal effect (16)(17)(18)(19). However, none of these studies have investigated the influence of this variability on the human nasal microbiota.…”
mentioning
confidence: 99%
“…Next-generation sequencing platforms (including SOLiD, Illumina and 454 sequencing) coupled with a powerful database and user-friendly software are beneficial for the analysis of a complex microbial community at deeper, more comprehensive level 17 , 22 . To date, next-generation high-throughput DNA sequencing techniques have been successfully applied in microbial community analyses of various environmental and organic samples, such as soil 23 , air 18 , water 24 , gut 20 , 25 , leaves and roots 26 . Over the past decade, several studies of fruit microbial communities have been conducted using next-generation sequencing methods 27 29 .…”
Section: Introductionmentioning
confidence: 99%
“…The microclimatic conditions of buildings, including relative humidity and dust concentration, are closely correlated with the fungal composition of the air (Kumari et al, 2016). A positive correlation has also been found between a high temperature in the pig house and the total number of coliforms and E. coli (Yao et al, 2010).…”
Section: Microclimatic Conditionsmentioning
confidence: 85%